Design and simulation analysis of an electrostatic actuator for improving the performance of scanning probe nanolithography - Tam, Le Van; Hieu, Dang Van; Vy, Nguyen Duy; Hung, Vu Ngoc; Hoang, Chu Manh (Vietnam Journal of Science and Technology, 2017)
In this paper, we design and simulate a micro-suspension based scanning probe for nanolithography using electrostatic actuation. The probe consists of a square plate with a pyramid tip at the center that is suspended by four beams. The entire probe is made of single silicon and is operated in air medium. Operation characteristics are analyzed by finite element method. The operation mode is symmetrical that overcomes the lateral displacement in the unsymmetrical operation mode of conventional scanning probe nanolithography, hence increasing the precision in lithographed nanostructures. The effect of electric field fringe and fixed electrode to the operation of the scanning probe are also analyzed in detail